PENGUATAN PEMBELAJARAN AKIDAH AKHLAK MELALUI PENDEKATAN RELIGIOUS CULTURE DI MADRASAH IBTIDAIYAH PLUS AL-HAMID BANJARMASIN - Hidayatul Jannah (ADDABANA: Jurnal Pendidikan Agama Islam, 2023)
Abstract: One of the sub-groups of Islamic Religious Education Subjects in Madrasas is Aqidah Akhlak. In learning aqidah morals students are not only required to understand the material, but are required to live and practice it in everyday life. Therefore, every madrasah, to meet the needs of students, especially in the development of Akidah Akhlak learning, seeks to develop religious activities as reinforcement in developing Aqidah Akhlak lessons, one of which is through religious cultural activities. This research is a qualitative research with the type of field research. In this study the author aims to describe the reality of an educational institution that applies religious culture as a form of strengthening the subject of aqidah morals. The results showed that the implementation of strengthening the Akidah Akhlak learning at MI Plus Al-Hamid Banjarmasin  through religious cultural activity es which were carried out with orderly planning and implementation, in the classroom carried out insightful activities for the development of moral aqeedah material and outside the classroom in the form of religious cultural activities and activities as a form of strengthening from the learning theory of aqidah morals. In this activity the forms of habituation, exemplary and internalization of religious cultural values are applied to students. The impact of strengthening Aqidah Akhlak learning through religious culture is a change in attitude from both the cognitive, affective and psychomotor domains. Keywords: Akidah Akhlak, Religious Culture, Strengthening. Abstrak: Salah satu sub rumpun Mata pelajaran Pendidikan Agama Islam di Madrasah adalah Akidah akhlak. Pada pembelajaran akidah akhlak peserta didik tidak hanya dituntut untuk memahami materi tersebut, namun dituntut untuk menghayati serta mengamalkannya dalam kehidupan sehari-hari. Oleh sebab itu setiap madrasah untuk memenuhi kebutuhan peserta didik terutama dalam pengembangan pembelajaran Akidah akhlak berupaya mengembangkan  kegiatan-kegiatan religius sebagai penguat dalam mengembangkan pelajaran Akidah akhlak salah satunya adalah melalui kegiatan budaya religius. Penelitian ini adalah penelitian kualitatif dengan jenis penelitian lapangan (field research). Pada Penelitian ini penulis bertujuan ingin menggambarkan realitas sebuah lembaga pendidikan yang menerapkan budaya religius sebagai bentuk penguatan dari mata pelajaran akidah akhlak. Hasil penelitian menunjukkan bahwa pelaksanaan penguatan pembelajaran Akidah Akhlak di MI Plus Al-Hamid Banjarmasin melalui kegiatan budaya religius yang dilaksanakan dengan perencanaan dan pelaksanaan yang tertib, di dalam kelas dilaksanakan kegiatan wawasan pengembangan materi akidah akhlak dan diluar kelas berupa aktifitas dan kegiatan budaya religius sebagai bentuk penguatan dari teori pembelajaran akidah akhlak. Pada kegiatan tersebut diterapkannya bentuk pembiasaan, keteladanan dan internalisasi nilai-nilai  budaya religius kepada peserta didik. Dampak dari penguatan pembelajaran Akidah akhlak melalui budaya religius adalah perubahan sikap baik dari ranah kognitif, afektif dan psikomotorik.  Kata kunci: Akidah Akhlak, Budaya Religius, Penguatan.